2019
DOI: 10.1002/chem.201805942
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polycyclic and Cage Siloxanes by Hydrolysis and Intramolecular Condensation of Alkoxysilylated Cyclosiloxanes

Abstract: The controlled synthesis of oligosiloxanes with well‐defined structures is important for the bottom‐up design of siloxane‐based nanomaterials. This work reports the synthesis of various polycyclic and cage siloxanes by the hydrolysis and intramolecular condensation of monocyclic tetra‐ and hexasiloxanes functionalized with various alkoxysilyl groups. An investigation of monoalkoxysilylated cyclosiloxanes revealed that intramolecular condensation occurred preferentially between adjacent alkoxysilyl groups to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…For the development of smart organic materials with target properties, many material scientists and engineers have tried to understand the thermodynamic and kinetic relationships between chemical structure, molecular packing structure and for meso-nanostructure, organic-inorganic hybrids, and functional amphiphiles. [39][40][41][42][43][44][45] In this context, there have been several reports about the synthesis and application of cyclosiloxanebased molecules, but the thermodynamic and kinetic relationships between the chemical structure, molecular packing structure, and resulting material properties of cyclosiloxane-based functional molecules need to be further studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the development of smart organic materials with target properties, many material scientists and engineers have tried to understand the thermodynamic and kinetic relationships between chemical structure, molecular packing structure and for meso-nanostructure, organic-inorganic hybrids, and functional amphiphiles. [39][40][41][42][43][44][45] In this context, there have been several reports about the synthesis and application of cyclosiloxanebased molecules, but the thermodynamic and kinetic relationships between the chemical structure, molecular packing structure, and resulting material properties of cyclosiloxane-based functional molecules need to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…[ 32–38 ] In particular, it is notable that cyclosiloxanes have advantages in view of geometry and dimensional diversity, multifunctionalization, relatively flexible building unit for meso‐nanostructure, organic–inorganic hybrids, and functional amphiphiles. [ 39–45 ] In this context, there have been several reports about the synthesis and application of cyclosiloxane‐based molecules, but the thermodynamic and kinetic relationships between the chemical structure, molecular packing structure, and resulting material properties of cyclosiloxane‐based functional molecules need to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…Octaarylsilsesquioxanes with reactive or non-reactive organic groups were synthesized from cyclotetrasiloxanetetraols and their sodium salts in the presence of ammonium catalysts [ 17 ]. Unsymmetrical silsesquioxane double-deckers of new types [ 17 , 18 , 19 , 20 , 21 , 22 ], the basket [ 23 ] and butterfly types [ 24 ], or siloxane cages were reported to be obtained by simple hydrolytic condensations of two cyclosiloxanes with an organomonosilane. They can be building blocks for diverse applications since materials based on them should have low dielectric constants and excellent thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, only a few studies on unsymmetrical silsesquioxane or siloxane cages have been reported because of the difficulty in obtaining a perfect Janus structure via a simple hydrolytic condensation of two organomonosilane precursors. Due to its unique chemical/physical properties related to type, number, and position of organic functional groups on a single molecule, the synthesis of asymmetrical structures has recently become an essential subject in chemistry [30,31,32,33,34,35]. Since the first report by the Laine group [30], to the most recent by the Kuroda group [31], on the synthesis of Janus cube octasilsesquioxane by the hydrolytic condensation of trimethoxy groups on cyclotetrasiloxanes rings, only our group has successfully synthesized a Janus cube from two different organic functional groups on cyclotetrasiloxane precursors [32].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its unique chemical/physical properties related to type, number, and position of organic functional groups on a single molecule, the synthesis of asymmetrical structures has recently become an essential subject in chemistry [30,31,32,33,34,35]. Since the first report by the Laine group [30], to the most recent by the Kuroda group [31], on the synthesis of Janus cube octasilsesquioxane by the hydrolytic condensation of trimethoxy groups on cyclotetrasiloxanes rings, only our group has successfully synthesized a Janus cube from two different organic functional groups on cyclotetrasiloxane precursors [32]. Furthermore, we also expanded to the synthesizing of an elongated core-sized Lantern Cage siloxane with the similar capping reaction between tetrakis(bromodimethylsiloxy)tetraphenylcyclotetrasiloxane and cyclotetrasiloxanetetraol [33].…”
Section: Introductionmentioning
confidence: 99%